Keputusan yang Mempengaruhi Wajib Pajak Untuk Mengajukan Sengketa Perpajakan Ke Pengadilan Pajak - Mayanti Mandasari Sitorus; Budiman Ginting; Sunarmi Sunarmi; Keizerina Devi (USU LAW JOURNAL, 2019)
Abstract. The existence of Tax Court is stipulated in Law No. 14/2002 on Tax Court which has the authority to check and hand down a verdict on tax dispute. Tax which is stipulated legally has coercion because it contains administrative and criminal sanctions imposed on taxpayers who do not report to tax authorities each month. It seems that many taxpayers who avoid their responsibility which bring about dispute between tax authorities and taxpayers.Tax dispute in taxation is a dispute between tax payers or tax guarantor and tax authorities as the result of the verdict which can be appealed to Tax Court according to the Tax Law, including lawsuit on the implementation of billing according to law on tax billing with forced letter. The research used juridical normative referred to legal norms and principles in legal provisions and court’s verdict, This law emphasizes on secondary data by studying and legal principles related to the position of tax court and legal remedy in settling tax dispute.The settlement of tax dispute consists of two kinds: appeal done based on Notice on Objection and lodged lawsuit on another verdict, besides the other objections and the verdicts related to tax billing and some factors which influence taxpayers to file tax dispute to the Tax Court.   Keywords: taxpayers, tax dispute, tax court